Ectopic expression of Kip‐related proteins restrains root‐knot nematode‐feeding site expansion. Issue 2 (10th April 2013) - Vieira, Paulo; Escudero, Carmen; Rodiuc, Natalia; Boruc, Joanna; Russinova, Eugenia; Glab, Nathalie; Mota, Manuel; De Veylder, Lieven; Abad, Pierre; Engler, Gilbert; de Almeida Engler, Janice
Summary: The development of nematode feeding sites induced by root‐knot nematodes involves the synchronized activation of cell cycle processes such as acytokinetic mitoses and DNA amplification. A number of key cell cycle genes are reported to be critical for nematode feeding site development. However, it remains unknown whether plant cyclin‐dependent kinase (CDK) inhibitors such as the Arabidopsis interactor/inhibitor of CDK (ICK)/Kip‐related protein (KRP) family are involved in nematode feeding site development. This study demonstrates the involvement of Arabidopsis ICK2/KRP2 and ICK1/KRP1 in the control of mitosis to endoreduplication in galls induced by the root‐knot nematode Meloidogyne incognita . Using ICK/KRP promoter‐GUS fusions and mRNA in situ hybridizations, we showed that ICK2/KRP2, ICK3/KRP5 and ICK4/KRP6 are expressed in galls after nematode infection. Loss‐of‐function mutants have minor effects on gall development and nematode reproduction. Conversely, overexpression of both ICK1/KRP1 and ICK2/KRP2 impaired mitosis in giant cells and blocked neighboring cell proliferation, resulting in a drastic reduction of gall size. Studying the dynamics of protein expression demonstrated that protein levels of ICK2/KRP2 are tightly regulated during giant cell development and reliant on the presence of the nematode. This work demonstrates that impeding cell cycle progression by means of ICK1/KRP1 and ICK2/KRP2 overexpression severely restricts gall development, leading to a marked limitation of root‐knot nematode development and reduced numbers of offspring.